2015
DOI: 10.1007/s11250-015-0984-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of constipation and its influence on post-parturient disorders in tropical sows

Abstract: The present study aimed to investigate the prevalence of constipation and its influence on farrowing duration and the evidence of post-parturient disorders in tropical sows and to evaluate the efficacy of a laxative supplementation during gestation and around farrowing on the incidence of constipation. Two experiments were performed in a commercial swine herd in Thailand. In experiment 1, the prevalence of constipation was determined in 96 gestating sows. Subsequently, 62 of them (64.6 %), with a severe to mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 10 publications
0
22
1
Order By: Relevance
“…Mild constipation around farrowing can be physiological due to low fiber content of the feed and restricted feeding (33). However, severe constipation in the peripartal period might cause serious problems, namely prolonged farrowing length and risk of PPDS (34)(35)(36). In our study, no significant differences were seen between treatment groups.…”
Section: Discussioncontrasting
confidence: 48%
“…Mild constipation around farrowing can be physiological due to low fiber content of the feed and restricted feeding (33). However, severe constipation in the peripartal period might cause serious problems, namely prolonged farrowing length and risk of PPDS (34)(35)(36). In our study, no significant differences were seen between treatment groups.…”
Section: Discussioncontrasting
confidence: 48%
“…It is well known that constipation is a common symptom for pregnant sows because gastrointestinal motility was decreased, and transit time was significantly prolonged during pregnancy, thereby resulting in increased water absorption and eventually low frequency and hard stools [ 26 ]. Constipation can lead to a series of distressing symptoms, including abdominal distension, gut obstruction, perforation, and increased farrowing duration, thereby affecting health of sows [ 27 ]. In this study, greater fecal water content was observed in sows fed SBP and WB diets when compared with those fed CON diets, suggesting that high fiber diets may alleviate the constipation severity in pregnant sows by retaining fecal water content.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that constipation is a common symptom for pregnant sows because gastrointestinal motility was decreased, and transit time was signi cantly prolonged during pregnancy, thereby resulting in increased water absorption and eventually low frequency and hard stools [25]. Constipation can lead to a series of distressing symptoms, including abdominal distension, gut obstruction, perforation, and increased farrowing duration, thereby affecting health of sows [26]. In this study, greater fecal water content was observed in sows fed SBP and WB diets when compared with those fed CON diets, suggesting that high ber diets may alleviate the constipation severity in pregnant sows by retaining fecal water content.…”
Section: Discussionmentioning
confidence: 99%